Repotenciación del horno eléctrico controlado por touch panel para tratamientos térmicos. - Guevara López, Andrés Sebastián (2019)
This project presents the repowering of an electric furnace results, to guarantee the fulfillment of different thermal treatments. The study is focused on obtaining the necessary temperature within the appropriate time parameters to perform annealing and mettle techniques. The electric furnace was built with materials such as: firebrick, sheet metal and refractory mortar, which were preserved during the applied redesign. Among the electronic elements that were used are: Kanthal A1 wire resistance of thread of 2 mm diameter, which solves all heating technical requirements and it is the most used in the oven industry for its reliability.In the control circuit the PLC 1200, the HMI screen and three relays were replaced by a REX temperature control, which allows to visualize the temperature to be reached for the camera and the temperature which it is on the wall inside the oven at every second. On the other hand, the calibers and types of conductors have a thermal protection, in other words, a fiberglass recovering to avoid its heating, it was obtained through based on the power obtained by its current. Finally, a radiation heat transfer analysis was applied to calculate the energy, power and resistivity that is required, so now the oven has a power of 6.9 KW and reaches 900 ° C in 2 hours.